2022
DOI: 10.3389/fendo.2022.1099818
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal laparoscopic partial adrenalectomy (RLPA) for 20-40 mm nonfunctional adrenal tumors in the day surgery mode

Abstract: ObjectivesTo investigate the outcome and safety of retroperitoneal laparoscopic partial adrenalectomy in the treatment of nonfunctional unilateral adrenal tumors in the day surgery mode.MethodsNineteen patients bearing nonfunctional unilateral 20-40 mm adrenal tumors were prospectively enrolled and underwent retroperitoneal laparoscopic partial adrenalectomy in the day surgery unit of our hospital between June 2021 and March 2022. All patients were diagnosed with non-functional adrenal tumors as outpatients be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In 2001, Horgan et al [23] reported the world's rst RALA surgery. Compared to traditional LA technology, RALA not only has advantages such as a 3D visual eld, ne manipulation and less tremor but also has virtues including less intraoperative bleeding, fewer surgical complications and a shorter LOS [24]. Some scholars have considered that RALA has advantages in dealing with complex AT, such as large volume tumors (> 6 cm) and patients with obesity.…”
Section: Patel Et Almentioning
confidence: 99%
“…In 2001, Horgan et al [23] reported the world's rst RALA surgery. Compared to traditional LA technology, RALA not only has advantages such as a 3D visual eld, ne manipulation and less tremor but also has virtues including less intraoperative bleeding, fewer surgical complications and a shorter LOS [24]. Some scholars have considered that RALA has advantages in dealing with complex AT, such as large volume tumors (> 6 cm) and patients with obesity.…”
Section: Patel Et Almentioning
confidence: 99%